The Existence of Indonesia’s National Law in Bridging the Gap Between National Developments and Local Wisdom - kadek Sarna (Sociological Jurisprudence Journal, 2022)
Development is always prone to causing negative impacts on the environment and marginalized communities, especially indigenous peoples. In fact, the local wisdom that is identical to indigenous people is often very detailed and accurately guiding the society in developing their life and also proved to be very effective to preserve the environment and ensure compatibility of community. In order to elaborate the existence of national law in bridging the gap between national development and local wisdom in Indonesia, this paper will try to elaborate part of development problems related to the protection of local wisdom in Indonesia’s national law as an effort in realizing sustainable development.